Radiofrequency-assisted liver resection: Technique and results. (September 2018) - Reccia, Isabella; Kumar, Jayant; Kusano, Tomokazu; Giakoustidis, Alexandros; Zanellato, Artur; Retsas, Phil; Habib, Nagy; Jiao, Long; Spalding, Duncan; Pai, Madhava
Abstract: Background: Radiofrequency (RF)-assisted liver resection allows non-anatomical liver resection with reduced blood loss and offers the opportunity for a combination of resection and ablation. However, there are still concerns with regard to postoperative complications related to this technique. In the present study, we discuss the technical aspects of RF-assisted liver resections and analyse the rate of perioperative complications, focusing on post-hepatectomy liver failure (PLF), bile leak and abscess, and mortality. Methods: Between 2001 and 2015, 857 consecutive open and laparoscopic elective RF-assisted liver resections for benign and malignant liver tumours were reviewed retrospectively to assess perioperative outcomes. Results: Median intraoperative blood loss was 130 mL, with 9.8% of patients requiring blood transfusion. Intra-abdominal collections requiring percutaneous drainage developed in 8.7% of all patients, while bile leak at resection margin developed in 2.8% of the cases. Major liver resection was performed in 34% of patients and the incidence of PLF was 1.5% with one directly related mortality (0.1%). Conclusion: RF-assisted liver resection has evolved into a feasible and safe technique of liver resection with an acceptable incidence of perioperative morbidity and a low incidence of PLF and related mortality. Highlights: Over 15 years, we have performed 857 radiofrequency (RF)-assisted liver resections. RF helped in reducing blood loss and blood transfusion during liver resection. RF-assisted liver resection showed low incidence of post-hepatectomy liver failure. RF-assisted liver resection allowed parenchymal sparing liver resection. In our experience, RF-assisted liver resection has evolved into a safe technique.